ANALISIS SISTEM ANTREAN PADA LOKET PENDAFTARAN POLIKLINIK SPESIALIS DI RS BALIMED - SUGIARI, KADEK DITA; SUMARJAYA, I WAYAN; JAYANEGARA, KETUT (E-Jurnal Matematika, 2021)
Hospital is one of the service facilities that is not free from queue problem. One example of this hospital is Balimed Hospital. At certain times, especially in the morning, there is a lineup of patients at the Balimed Hospital’s Specialist Polyclinic. In order to maximize service, it is necessary to analyze the queuing system by applying the queuing theory. This study focuses on queues at the Balimed Hospital’s Specialist Polyclinic in Internal Disease. After conducting the research, it was found that the model used at the Specialist Polyclinic in Internal Disease is . With this model, the queuing system at Balimed Hospital's Specialist Polyclinic in Internal Disease is in steady state condition because ???? < 1 . The measures of performance for queuing system at Balimed Hospital’s Specialist Polyclinic in Internal Disease is the average number of patients in queue   is 0,1 patient or it can be said that there is almost no patient in queue because the value of   is close to 0, the average number of patients in system   is 1 patient, the average waiting time for patients in queue   is 1 minute, and the average time spent by patients start from queuing until being served   is 2,5 minutes. The queuing system has been effective, it can be seen from the short waiting time for patients.